THE REGULARITY OF VERTICAL CRUSTAL MOVEMENTS OF THE WESTERN SLOPES OF THE PETER THE GREAT RANGE - Enman S.V.; Raizman A.P. (My University, 1988)
The results of relevellings made in 1948 and 1969-1975 along the Obi-Hingou profile, which is a part of the Garm test area, are analysed. Different characteristics of slow movements in the separate parts of the levelling line divided by faults were obtained by using the displacement velocities of the Earth's surface in each separate section of the profile (from the results of repeated levellings). The uplift of the Peter the Great Range is determined against the background of subsidence in the Tadjik Depression. The exact values of maximum displacements ( ≈ 7 mm ) were determined and the radius of the deformation zone (12-13 km) was established for earthquakes with M = 4.5-5.